2013
DOI: 10.1007/s00784-013-1002-7
|View full text |Cite
|
Sign up to set email alerts
|

Penetration kinetics of four mouthrinses into Streptococcus mutans biofilms analyzed by direct time-lapse visualization

Abstract: The mouthrinses tested showed different levels of biofilm penetration. The essential oil rinse was superior to other rinses by all three of the in vitro measurements performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 57 publications
4
26
0
1
Order By: Relevance
“…However, the conventional tests of antibiotic susceptibilities, such as the Kirby-Bauer (disc diffusion) test or broth dilution measurements exclude the conditions of biofilm formation and thus do not reflect the effectiveness of antimicrobials in vivo. Moreover, fluorescence-induced confocal laser scanning microscopy (CLSM) has been shown to be a powerful technique that reveals a three-dimensional structural image with microscopic resolution and allows for quantitative assessment of the bioðlm constituents [4][5][6][7]. However, since the extracellular polymeric substance (EPS) is a complex mixture of different biopolymers with a large number of potential binding sites [8], it is difficult to design a suitable protocol to stain the entire EPS, which limits the application of CLSM in EPS identification and quantification.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conventional tests of antibiotic susceptibilities, such as the Kirby-Bauer (disc diffusion) test or broth dilution measurements exclude the conditions of biofilm formation and thus do not reflect the effectiveness of antimicrobials in vivo. Moreover, fluorescence-induced confocal laser scanning microscopy (CLSM) has been shown to be a powerful technique that reveals a three-dimensional structural image with microscopic resolution and allows for quantitative assessment of the bioðlm constituents [4][5][6][7]. However, since the extracellular polymeric substance (EPS) is a complex mixture of different biopolymers with a large number of potential binding sites [8], it is difficult to design a suitable protocol to stain the entire EPS, which limits the application of CLSM in EPS identification and quantification.…”
Section: Introductionmentioning
confidence: 99%
“…Diluted solutions were centrifuged at 2,000 g for 10 minutes to remove any debris, and the supernatants were filter sterilized. The saliva solution was used to coat discs with salivary pellicles [18,23]. All study protocols were approved by the Ethics Committee for Clinical Research of Niigata University (approval no.…”
Section: Saliva Collection and Processingmentioning
confidence: 99%
“…Wakamatsu et al have reported the penetration kinetics of mouthrinses into in vitro Streptococcus mutans biofilms by direct time-lapse microscopic analysis. The antimicrobial penetration was critically restricted within 30 s of exposure; the average penetration velocity was ranging from 4.2 to 30.1 µm/min [13]. This phenomenon can be explained by retarded penetration due to degradation and/or modification by the biofilm matrix.…”
Section: Introductionmentioning
confidence: 97%